Affectors on the Manufacturing Sector’s Labor Absorption - Dina Hadia; Octafia, Sri Mona; Weriframayeni, Annisa (AFEBI Economic and Finance Review, 2024)
Economic development that focuses on the industrial sector is a major driving force of economic growth, including in providing employment for the workforce. Therefore, this study aims to determine the effect of industrial sector investment, industrial sector wages, industrial sector GRDP, and the number of industries on labor absorption in the manufacturing industry sector in West Sumatra. The analysis method used in this study is Multiple Regression Analysis using time series data from 1996-2012. The independent variables used in this study are industrial sector investment, industrial sector wages, industrial sector GRDP, and the number of industries, while the dependent variable is labor absorption in the manufacturing sector. The results of this study show that simultaneously all four independent variables in this study have an effect on the dependent variable. However, partially, the industrial sector investment variable does not have a significant effect on labor absorption, and the industrial sector GRDP variable has a negative and significant effect on labor absorption, while the wage and number of industries variables have a positive and significant effect on labor absorption in the manufacturing industry sector in West Sumatra.